A FORMAL MODEL OF THE AGENT-BASED SIMULATION FOR THE EMERGENCY EVACUATION PLANNING - Amir, Mohammad Idil Haq; Rosyidah, Fifi Alfiana; Lee, Gyu M (International Journal of Industrial Engineering: Theory, Applications and Practice, 2021)
Recently, the number and size of natural or manmade disasters have increased, leading to significant casualties and enormous economic losses. Disaster is any occurrence that causes damage, ecological disruption, human life or economic loss in a particular area. Massive disasters such as a nuclear disaster can cause a massive damage to the environment and human life. Disaster evacuation is the only way to save the human life after a disaster occurrence. However, the development of an evacuation plan requires many considerations on several factors such as the number of people, the number of shelters, the road network, the traffic congestions and more. The simulation for disaster evacuation can be a useful decision-making tool for the evacuation planner by conducting various evacuation scenarios for analyzing the best evacuation plan. This paper presents a formal model of the agent-based simulation (ABS) for the development of a nuclear disaster evacuation planning tool. In this effort, the agent represents the people that evacuate during the nuclear disaster through the road network. The agent movement behavior is determined by the knowledge and the reward function by implementing the Markov Decision Process (MDP) on the road network. A simulation tool is developed with experiments to demonstrate the effectiveness of the proposed formal model. The simulation results provide an insight for the evacuation planner in designing an efficient evacuation plan in a certain disaster event. The proposed formal model can be used for a useful tool to develop the evacuation strategy.